Menumbuh Kembangkan Jiwa Kewirausahaan Santri Untuk Kemandirian Pondok Pesantren Bahrul Maghfiroh Kota Malang - Lutfi Aji Nursyah Alam; Afi Rachmat Slamet; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
Abstract Islamic boarding school is one of the non-formal educational institutions spread across Indonesia. Pesantren is a unique form of “community” environment and has positive life values and religious education. However, at this time, along with the development of the era, Islamic boarding schools do not only teach about religious knowledge, nowadays Islamic boarding schools are experiencing an extraordinary shift in values, especially with regard to the world of work. If in the past, pesantren was still considered taboo when talking about work or worldly affairs, let alone developing entrepreneurship, now the development of entrepreneurship in the pesantren environment has become a necessity, especially if this is associated with pesantren education which prioritizes independence and hard work. With this entrepreneurial spirit will give birth to various types of creative businesses that are in accordance with local potential and resources, so that the economic independence of students will be realized. This research was conducted with the aim of providing an overview in developing the entrepreneurial spirit of students To provide an overview of the level of independence of Islamic Boarding School. Keywords : Entrepreneurship, Independence, Islamic Boarding School